Orthogonal Frequency Division Multiplexing with Diversity for Future Wireless Systems. - Le, Khoa N. (Bentham Science Publishers, 2012)
The book examines several aspects of Orthogonal Frequency Division Multiplexing (OFDM) employing linear diversity techniques such as inter-carrier interference, bit error rate, peak to average power and inter-block interference. It should be a useful reference for readers interested in modern wireless communication systems.